Assessment of Dural Ectasia Using Computed Tomodensitometry as a Criterion in Marfan Syndrome. Issue 2 (March 2019) - Chuzel, Quentin; Dupuis-Girod, Sophie; Rousset, Matthieu; Decharry, Charlotte; Decullier, Evelyne; Pialat, Jean-Baptiste
Abstract : Objective: The aim of this study was to reevaluate dural ectasia criteria in Marfan syndrome patients fulfilling the revised Ghent criteria. Methods: Lumbar computed tomography scans of 19 Marfan patients and 30 matched control subjects were retrospectively assessed. Dural sac ratio (DSR), nerve root sleeve diameter, pedicle width, and a scalloping or meningocele presence were each assessed by 2 readers blinded from the diagnosis. Mann-Whitney-Wilcoxon tests compared the patient and control groups. Receiver operating characteristic curve analysis and multivariate models determined the optimal cutoff value. Results: A DSR value greater than 0.69 at L5 (DSR-L5) such as L4 scalloping of more than 2.65 mm (scall-L4) and 6 or more vertebrae showing a scalloping of more than 3 mm (6-scall) were found very specific but with limited sensitivity. Multivariate model combining DSR-L5 + scall-L4 showed good positive predictive value, whereas model combining DSR-L5 + 6-scall showed good negative predictive value. Conclusions: Assessment of DSR and vertebral scalloping allows valuable depiction of dural ectasia in Marfan syndrome patients.